1994
DOI: 10.1063/1.111628
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic properties of CoxNi1−x/Pt multilayers

Abstract: We have prepared CoxNi1−x/Pt multilayers by evaporation under ultrahigh vacuum conditions and studied their magnetic and magneto-optical properties. The addition of Co to Ni leads to an increase in both the surface anisotropy and TC. It is found that the surface anisotropy Ks of CoxNi1−x/Pt multilayers can be expressed as the sum of Ks of Ni/Pt and of Co/Pt times their respective concentration. In Co0.3Ni0.7/Pt multilayers, for t(Co,Ni)=0.45 nm, one observes a perpendicular M-H loop with a good rectangularity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
11
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 6 publications
4
11
0
Order By: Relevance
“…The K s determined in this way compares well with results from magnetic layer thickness series from various authors (e.g. [8]). From this good match we conclude that the choice of the argon pressure at which the multilayer is in the stress-free state is justified.…”
Section: Resultssupporting
confidence: 71%
“…The K s determined in this way compares well with results from magnetic layer thickness series from various authors (e.g. [8]). From this good match we conclude that the choice of the argon pressure at which the multilayer is in the stress-free state is justified.…”
Section: Resultssupporting
confidence: 71%
“…1 is calculated using the above values and it is seen that the experimental points align very well. This result is similar to what we had obtained in Co-Ni/Pt system [6] and thus brings additional support to our hypothesis that the contribution from magneto-elastic effects to Ks is negligible. Let us also recall that the magnetostriction in Co-Ni alloys varies in a complex manner and even changes sign [11].…”
Section: Magnetic Anisotropysupporting
confidence: 81%
“…This point is of great importance for application. We showed that the surface anisotropy (Ks ) in this system varied linearly with the Co concentration which is of fundamental importance as we have discussed in our work [6]. We attributed this behaviour also to the fact that the magneto-elastic contribution to Ks is negligible if not absent.…”
mentioning
confidence: 50%
See 1 more Smart Citation
“…Lower stability of the small stored bits is then obtained. The high Curie temperature of the CoIPt, which is responsible of a rather low writing sensitivity, can be reduced by alloying cobalt with nickel [9]. The writing sensitivity can also be improved using a seed layer of mixed tin and indium oxide [lo].…”
Section: Multilayers Of Very Thin Films (Less Than 1 or 2 Nm) Of Colnmentioning
confidence: 99%